2001
DOI: 10.1177/089686080102100405
|View full text |Cite
|
Sign up to set email alerts
|

Diverticular Disease and Treatment with Gastric Acid Inhibitors do not Predispose to Peritonitis of Enteric Origin in Peritoneal Dialysis Patients

Abstract: Objective Enteric peritonitis (EP) is an infrequent complication of peritoneal dialysis (PD), with severe consequences for peritoneal membrane viability and patient outcome. Factors such as diverticular disease and gastric acid inhibitors have been implicated in its appearance. We investigated several risk factors, including those mentioned below, that can influence the development of EP. Design Retrospective cross-sectional study. Setting Tertiary-care public university hospital. Patients Fifty-seven PD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…A total of 829 people were included in our meta-analysis. Two-thirds (n = 4) of studies found that GAS use did not relate to an increased risk of enteric peritonitis, 19,[23][24][25] whereas the other two studies showed that GAS use increased that risk. 17,18 Obvious heterogeneity was not observed, so a fixed-effects model was used.…”
Section: Outcome Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…A total of 829 people were included in our meta-analysis. Two-thirds (n = 4) of studies found that GAS use did not relate to an increased risk of enteric peritonitis, 19,[23][24][25] whereas the other two studies showed that GAS use increased that risk. 17,18 Obvious heterogeneity was not observed, so a fixed-effects model was used.…”
Section: Outcome Resultsmentioning
confidence: 94%
“…Thus, heterogeneity might have derived from these low-quality studies. 17,19,23 Due to these limitations, our results should be interpreted with caution. Randomized, prospective studies with a large number of cases and an updated, high-quality meta-analysis are needed to confirm our findings.…”
Section: Recent Meta-analyses On Patients With Cirrhosis Demonstratedmentioning
confidence: 85%
See 3 more Smart Citations